Intestinal permeability in participants with thermal injury: A case series from a prospective, longitudinal study (HESTIA). Issue 3 (July 2020) - Tipple, Craig; Moiemen, Naiem S.; Ioannou, Chris; Paglione, Marcella; Goodson, Summer; McGee, Kirsty; O'Neil, Donna; Winder, Catherine L.; Barnett, Carly; Wolf, Amaya I.; Bamford, Amy L.; Dunn, Warwick B.; et al.
Highlights: Lactulose/mannitol (L/M) ratio is a useful measure of small intestine permeability. Elevated gut permeability was observed in thermal injury versus healthy participants. Potential pattern seen between permeability increases and degree and timing of injury. Serum occludin and sCD14 are potential biomarkers of raised intestinal permeability. Improving intestinal integrity may be a useful therapeutic strategy in future trials. Abstract: Objectives: Severe thermal injury (TI) has been associated with increased intestinal permeability and the development of multiple organ dysfunction syndrome. The aim of this case series from a prospective, longitudinal study is to describe the impact of TI on intestinal permeability in critically ill participants with TI versus observations from healthy participants. Methods: Participants with TI ≥ 15% total body surface area and healthy participants were recruited into the study. The co-primary endpoints were lactulose/mannitol [L/M] ratio (a) within 24 h of hospital admission and (b) over time. Exploratory endpoints included fractional excretion of sucralose and changes in blood biomarkers (eg, occludin and soluble CD14 [sCD14]). Clinical severity of injury, demographic and morbidity data were also collected. Results: Fourteen healthy participants and three participants with TI were enrolled. Case histories for two of the three participants with TI showed peak L/M-measured permeability ~10-fold higher than healthy participants, with a clear pattern between degree and timing of injury and increases in permeability. Serum occludin and sCD14 levels were elevated in all three participants with TI versus healthy participants. The study was terminated early with a reduced sample size and duration than planned. Conclusion: Observed changes in L/M-measured permeability of participants with TI support the existing literature of raised intestinal permeability in critically ill individuals, with increases seen in the first few days of hospital admission. Occludin and sCD14 are identified as potential surrogate markers of raised permeability but require validation in larger studies.